2019
DOI: 10.1063/1.5099589
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of simulation and experiments for multimode aerodynamic breakup of a liquid metal column in a shock-induced cross-flow

Abstract: While the mechanisms that drive breakup and aerodynamic dispersion of traditional liquids such as water have been extensively studied, it is not yet clear if models for traditional liquids can be used to accurately describe the behavior of molten metals. In this paper, multiphase simulations with the interface-capturing combined level-set volume-of-fluid approach are used to provide time-resolved morphology and breakup data for a liquid column subject to a shock-induced cross-flow. For the first time, numerica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
3
8
0
Order By: Relevance
“…Variation can arise due to experimental uncertainties. As observed in the literature (Chen et al 2018;Arienti et al 2019;Hopfes et al 2021b), the uncertainty in droplet deformation increases with an increase in the Weber number values. Here, deformation is measured at much higher Weber number values, and higher uncertainty is expected.…”
Section: Quantitative Comparison For Three Test Casessupporting
confidence: 75%
See 4 more Smart Citations
“…Variation can arise due to experimental uncertainties. As observed in the literature (Chen et al 2018;Arienti et al 2019;Hopfes et al 2021b), the uncertainty in droplet deformation increases with an increase in the Weber number values. Here, deformation is measured at much higher Weber number values, and higher uncertainty is expected.…”
Section: Quantitative Comparison For Three Test Casessupporting
confidence: 75%
“…Within the experimental uncertainty, a similar behaviour of droplet deformation is observed till the first instance of droplet breakup (t * ∼ 0.6, in all cases). Previous studies (Chen et al 2018;Arienti et al 2019;Hopfes et al 2021a) have also shown a similar behaviour of early stage droplet deformation between Galinstan and DI water test cases. After t * > 0.6, droplet atomisation begins, making it difficult to measure the cross-stream diameter accurately.…”
Section: Quantitative Comparison For Three Test Casessupporting
confidence: 68%
See 3 more Smart Citations